Numerical Investigations on Solar Chimney Inclination Angle for Room Ventilation - Dr. Abbas J. Jubear, Ass.Prof.; Dhahi Ghareer, Ali (International Journal of Engineering and Technology, 2018)
This paper presents a developed model of the  roof solar chimney (RSC) and thermal performance predict using the simulation program Ansys Fluent 18 and solid work software 2016. This work is carried out under the climatic conditions of the city of Kut-Iraq. This study is based on the analysis the thermal performance of the solar chimney at different inclination angles (30o, 45o, and 60o) with south and west direction. The results of the analysis showed that the solar chimney at a 45° angle gives the best thermal performance and provides a good ventilation rate. This model has been developed with the use of multi chimney tilted at a 45° angle in the same room. The arrangement of solar chimneys is in the two directions, one in the south and  the second  in the western direction. In this study, a several parameters were studied (angle of inclination, solar intensity, chimney direction, and ambient temperature), which significantly affect ventilation rates. The results showed that the use of the developed model leads to improved ventilation rates by 31.9 % and reduce average temperature are 1.34 oC.
Keywords: Natural ventilation; Multi chimney; roof solar chimney; thermal performance.